Farelo residual de milho com e sem enzima em dietas para frango de corte - VALADARES, Camila Guedes (2014)
Corn is the main ingredient used in energy rations of broilers, significantly contributing to the larger fraction of the final cost of the ration. Research is being carried out with alternative in order to remedy the final value of food production. However, there is little literature on the chemical composition of these alternative so that they can enter in the formulation of diets, thus meeting the nutritional requirements of the animal ingredients. In broilers, we highlight the use of agro-industrial byproducts hominy feed (FRM), and alternative in poultry production. As by-products, these foods may have low nutrient digestibility or availability for use in animal diets. Thus, many studies are being conducted with the use of conventional foods or not the use of enzymes / enzyme complexes, which will aim to increase the availability of nutrients for the best utilization of the animal, thus generating a satisfactory response production. Given the context of an experiment metabolism to evaluate the nutritional value and determine the metabolizable energy of hominy feed (FRM) with and without the use of alpha amylase enzyme was performed. Metabolism of an experiment with 180 male Cobb chicks with 14 days allotted in a completely randomized design with six treatments, five replicates of six birds per treatment was performed. The experimental diets were: T1: basal diet (RR), T2: T1 60% + 40% of FRM, T3: RR + enzyme, T4: T1 60% + 40% of FRM with enzyme addition, T5: RR with replacement 100% of corn by FRM and T6: RR with 100% replacement of corn by FRM with enzyme addition. The chemical composition of the FRM was: 88.33% dry matter (DM), 10.23% crude protein (CP), 15.44% of ether extract (EE), 4.33% ash (CZ) and 4555 kcal / kg of gross energy (GE). The coefficients of apparent metabolizable for FRM with and without addition of enzyme were 73.37 and 76.33% for MS (p = 0.0136), 70.44 and 70.39% for CP (p = 0 , 9595) and 74.79 and 76.77% for EB (p = 0.0128). The values of apparent metabolizable energy (AME) and AME corrected for nitrogen retention (AME) for the FRM (on natural basis) were 3322 ± 19 and 3241 ± 18 kcal / kg and 3334 ± 16 and 3261 ± 17 kcal / kg, respectively, with and without addition of enzyme. The addition of the enzyme had no statistically significant effect on the AME and AME. Enzyme addition improved metabolization coefficient of dry matter and energy.